Impulsivity Kills Some Who Did Not Plan to Die by Suicide: Evidence From Chinese Rural Youths. (September 2019) - Lin, Lin; Zhao, Sibo; Zhang, Jie
This study aimed to compare the mental disorders, psychological factors, and suicidal intent between high- and low-impulsivity Chinese rural young suicides. Rural young women and men aged 15 to 34 years who died by suicide and various risk factors were examined. The data were obtained using psychological autopsy method with instruments as Dysfunctional Impulsivity Scale, the Structured Clinical Interview for DSM-III-R, Beck Hopeless Scale, Social Support Index, Coping Response Inventory, Hamilton Depression Rating Scale, and Beck Suicide Intent Scale. Compared with low-impulsivity suicides, the high-impulsivity suicides were younger, had less mental disorders, owned less social support, scored lower on approach coping and higher on avoidance coping, and scored a lower score on the Suicide Intent Scale. Characteristics of high-impulsivity suicides differed significantly from low-impulsivity suicides in rural China. It was important to develop different prevention and intervention strategies to reduce the suicide rate in China.